Impact of a Diesel High Pressure Common Rail Fuel System and Onboard Vehicle Storage on B20 Biodiesel Blend Stability - Christensen, Earl; McCormick, Robert L.; Sigelko, Jenny; Johnson, Stuart; Zickmann, Stefan; Lopes, Shailesh; Gault, Roger; Slade, David (SAE International journal of fuels and lubricants, 2016)
Adoption of high-pressure common-rail (HPCR) fuel systems, which subject diesel fuels to higher temperatures and pressures, has brought into question the veracity of ASTM International specifications for biodiesel and biodiesel blend oxidation stability, as well as the lack of any stability parameter for diesel fuel. A controlled experiment was developed to investigate the impact of a light-duty diesel HPCR fuel system on the stability of 20% biodiesel (B20) blends under conditions of intermittent use and long-term storage in a relatively hot and dry climate. B20 samples with Rancimat induction periods (IPs) near the current 6.0-hour minimum specification (6.5 hr) and roughly double the ASTM specification (13.5 hr) were prepared from a conventional diesel and a highly unsaturated biodiesel. Four 2011 model year Volkswagen Passats equipped with HPCR fuel injection systems were utilized: one on B0, two on B20-6.5 hr, and one on B20-13.5 hr. Each vehicle was operated over a one-hour drive cycle in a hot running loss test cell to initially stress the fuel. The cars were then kept at Volkswagen’s Arizona Proving Ground for two (35°C average daily maximum) to six months (26°C average daily maximum). The fuel was then stressed again by running a portion of the one-hour dynamometer drive cycle (limited by the amount of fuel in the tank). Fuel rail and fuel tank samples were analyzed for IP, acid number, peroxide content, polymer content, and ester profile. The HPCR fuel pumps were removed, dismantled, and inspected for deposits or abnormal wear. Analysis of fuels collected during initial dynamometer tests showed no impact of exposure to HPCR conditions. Long-term storage with intermittent use showed that IP remained above 3 hours, acid number below 0.3 mg KOH/g, peroxides low, no change in ester profile, and no production of polymers. Final dynamometer tests produced only small changes in fuel properties. Inspection of the HPCR fuel pumps revealed no deposits or abnormal wear for any fuel. The results provide some confidence that the ASTM D7467 stability requirement of 6 hr. minimum IP for B6 to B20 blends provides adequate protection for modern engine fuel systems.